Relationship between periodontal disease and butyric acid produced by periodontopathic bacteria - Michihiro Shirasugi; Maki Nakagawa; Keisuke Nishioka; Toshiro Yamamoto; Takaaki Nakaya; Narisato Kanamura (BMC, 2018)
Abstract Background Periodontopathic bacteria such as Porphyromonas gingivalis produce a large amount of butyric acid as a metabolite. Though butyric acid has been reported to have an anti-inflammatory effect on inflammatory diseases in the gastrointestinal tract, it has been suggested to contribute to the progression of periodontal disease in the oral cavity. The concentration of butyric acid in periodontal tissue of patients with periodontitis patients is reported to increase with the progress of the periodontal disease state. However, the influence of butyric acid on periodontal disease progression is not well known. Main text In this review, we have considered the relationship between butyric acid and periodontal disease with respect to the findings reported till date and the knowledge we newly obtained [Shirasugi M et al. Biochem Biophys Res Commun, 2017]. We have studied the relationship between butyric acid and periodontal disease by analyzing the effect of butyric acid on normal human gingival fibroblasts, which are a major component of periodontal tissue. We observed that gingival fibroblasts underwent cytostasis and apoptosis via extrinsic and intrinsic pathways upon long-term exposure to butyric acid. In addition, we showed that TNF-α produced by gingival fibroblasts treated with butyric acid plays an important role in inducing exogenous apoptosis. Conclusion Butyric acid produced by periodontopathic bacteria may promote progress of the periodontal disease state. Butyric acid is known to act as an HDAC inhibitor. Thus, we believe that advanced epigenetic analysis of the effects of butyric acid on gingival fibroblasts will help elucidate the periodontal disease pathology and facilitate discovery of new targets for periodontal disease treatment.